2019
DOI: 10.1155/2019/7034620
|View full text |Cite
|
Sign up to set email alerts
|

Doping Efficiency in Cobalt-Doped ZnO Nanostructured Materials

Abstract: Nanostructured ZnO thin films doped with cobalt from 5% to 20% were grown on glass substrates by a low-temperature chemical bath deposition (CBD) technique. We compared the doping efficiency of incorporating cobalt in ZnO nanostructured samples doped with cobalt via cobalt nitrate and cobalt chloride. The concentration of cobalt incorporated into the ZnO matrix was precisely determined using inductively coupled plasma mass spectroscopy (ICP-MS). Scanning electron microscopy (SEM) images showed that only at a 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…The detailed process of fabricating ZnO and cobalt doped ZnO nanorods using chemical bath deposition (CBD) was discussed in detail in our previous studies. [35][36][37][38][39][40][41] For CuO nanostructures, the growth mechanism was a modied chemical bath deposition (CBD) method in which equimolar 0.1 M of copper nitrate trihydrate (Cu(NO) 3 $3H 2 O) and hexamethylenetetramine (C 6 H 12 N 4 ) was dissolved in deionized water under constant stirring. Few drops of ammonium hydroxide solution (30-33% NH 3 in H 2 O) was added to the resulting precursor solution until the pH reached 8.…”
Section: Experimental Details and Characterization Techniquesmentioning
confidence: 99%
“…The detailed process of fabricating ZnO and cobalt doped ZnO nanorods using chemical bath deposition (CBD) was discussed in detail in our previous studies. [35][36][37][38][39][40][41] For CuO nanostructures, the growth mechanism was a modied chemical bath deposition (CBD) method in which equimolar 0.1 M of copper nitrate trihydrate (Cu(NO) 3 $3H 2 O) and hexamethylenetetramine (C 6 H 12 N 4 ) was dissolved in deionized water under constant stirring. Few drops of ammonium hydroxide solution (30-33% NH 3 in H 2 O) was added to the resulting precursor solution until the pH reached 8.…”
Section: Experimental Details and Characterization Techniquesmentioning
confidence: 99%
“…The grain size reduced with increase of cobalt doping concentration whereas it forms densely packed network. It is clearly observed that for increase in cobalt concentration from 1% to 7% the grain size was found to be decreased [33,34] according to the figures 3(d), (e). Here it was noticed that the dopant deteriorate the degree of crystallization through its substitution.…”
Section: Surface Morphologymentioning
confidence: 76%
“…An aqueous solution of 0.1 M of CoCl 2 .6H 2 O supplied from Merck Chemicals (Germany) was used to prepare thin films of Co 3 O 4 [25], and 0.1 M of Manganese chloride MnCl 2 •4H 2 O was used as doping agent with a concentration of 1% and 3% to obtain Mn doped cobalt chloride [26]. A few drops of HCl were added to obtain a homogeneous solution.…”
Section: Methodsmentioning
confidence: 99%